Peripheral blood microR-146a and microR-29c expression in children with Mycoplasma pneumoniae pneumonia and its clinical value - Jingcai Wang; Chunyan Guo; Lixin Yang; Peng Sun; Xiaoqing Jing (BMC, 2023)
Abstract Background We investigated changes in microR-29c and microR-146a expression in the serum of children with Mycoplasma pneumoniae pneumonia, analysed their relationship with inflammatory factors and disease severity, and evaluated their diagnostic significance. Methods Fifty-six children with Mycoplasma pneumoniae pneumonia were enrolled as the Mycoplasma pneumoniae pneumonia group; 37 healthy children were enrolled as the control group. The microR-29c or microR-146a serum expression levels were determined using real-time quantitative reverse transcription polymerase chain reaction. Interleukin-17, tumour necrosis factor-alpha, and interleukin-1 beta levels were detected using enzyme-linked immunosorbent assay. The correlation between serum microR-29c or microR-146a expression and inflammatory factors was analysed using the Pearson's method. Receiver operating characteristic curves were used to evaluate the diagnostic value of serum microR-29c, microR-146a, and their combined detection in Mycoplasma pneumoniae pneumonia. Results Compared with that in healthy children, the microR-29c and microR-146a serum levels were significantly downregulated in children with Mycoplasma pneumoniae pneumonia; the decrease was more obvious in children with severe cases than that in those with mild cases. In addition, microR-29c and microR-146a were negatively correlated with increased expression of interleukin-17, tumour necrosis factor-alpha, and interleukin-1 beta. Receiver operating characteristic curves showed that a combination of microR-29c and microR-146a was highly suitable for diagnosing Mycoplasma pneumoniae pneumonia. Conclusion Serum microR-29c and microR-146a were underexpressed in children with Mycoplasma pneumoniae pneumonia, and diagnostic accuracy was significantly improved with combined microR-29c and microR-146a detection. Therefore, both microR-29c and microR-146a levels can be used as biomarkers for the diagnosis of Mycoplasma pneumoniae pneumonia.